1974
DOI: 10.1073/pnas.71.12.5052
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Lens-Like Structures from Newt Iris Epithelial Cells In Vitro

Abstract: (10,11,27,28).We have shown that the switch from pigmented retinal cells of 9-day-old check embryos into lens cells occurs in clonal cell culture without interactions with other cell types (14). The question then arises whether this approach can be extended to iris epithelial cells of newts which possess the capacity for Wolffian regeneration in vivo. This communication describes the differentiation of lens-like structures in cultures of dissociated iris epithelial cells of adult newts. MATERIALS AND METHODSTw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(55 citation statements)
references
References 26 publications
1
54
0
Order By: Relevance
“…Results of the present study are also being supported by the finding of Eguchi et al (1974). In their finding, they observed that under certain conditions, dedifferentiation of extra ordinary cells enable the acquisition of new and higher developmental potencies.…”
Section: Discussionsupporting
confidence: 78%
“…Results of the present study are also being supported by the finding of Eguchi et al (1974). In their finding, they observed that under certain conditions, dedifferentiation of extra ordinary cells enable the acquisition of new and higher developmental potencies.…”
Section: Discussionsupporting
confidence: 78%
“…This is manifest in different ways depending on tissue type. Iris pigmented epithelial cells transdifferentiate and proliferate during lens regeneration (Eguchi et al, 1974). Multinucleate newt myotubes and myofibres re-enter the cell cycle and undergo conversion to mononucleate cells during limb and tail regeneration (Echeverri et al, 2001;Kumar et al, 2000;Lo et al, 1993;Velloso et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that in different experimental systems the extent of aggregation of cells in culture can influence cell differentiation (for a review, see 10). In tissue culture, newt dorsal iris fails to transdifferentiate into lens unless retina or pituitary is present (32, 12), but under cell culture conditions iris epithelial cells can transdifferentiate into lens fibers (18,13). Moreover, in tissue culture lens fiber formation from hatched chick lens epithelium also does not occur unless the retina or pituitary is present.…”
Section: Experiments VI In Vitro Culture Of Outer Cornea and Pericornmentioning
confidence: 99%